Nestle Company Working Capital Management - Afrida Dinarintasitepu; Badnatul Nafis; Rico Nur Ilham; Hafiz Raza Ali (International Journal of Economics, Management and Accounting (IJEMA), 2023)
Every company needs capital to finance operations, then the funds that have been issued go back into the company from the sale of goods that have been produced by the company earlier. Elements of working capital such as inventories, accounts receivable, and cash essentially experience turnover until they return to being in the form of cash with a higher value than the cash originally issued. This investment is what is needed in the company because it is very flexible so that it is able to adjust the value of goods to market fluctuations that are increasing and decreasing.